Microwave Assisted Synthesis, Characterization and Biological Activities of Ferrocenyl Chalcones and Their QSAR Analysis - Yadav, Dinesh K.; Kaushik, Parshant; Pankaj,; Rana, Virendra S.; Kamil, Deeba; Khatri, Dilip; Shakil, Najam A. (Frontiers in Chemistry, 2019)
A new microwave method (MM) has been developed for the synthesis of a series of sixteen substituted ferrocenyl chalcones using acetylferrocene (1) with different benzaldehydes, benzaldehyde (2a), 4-bromobenzaldehyde (2b), 4-fluorobenzaldehyde (2c), 2-chlorobenzaldehyde (2d), 2-bromobenzaldehyde (2e), 4-methoxybenzaldehyde (2f), 4-dimethylaminobenzaldehyde (2g), 3,4,5-trimethoxybenzaldehyde (2h), 3-hydroxybenzaldehyde (2i), 4-benzyloxybenzaldehyde (2j), 2-nitrobenzaldehyde (2k), 3-nitrobenzaldehyde (2l), 4-nitrobenzaldehyde (2m), 2,4-dichlorobenzaldehyde (2n), 2,6-dichlorobenzaldehyde (2o) and 4-hydroxybenzaldehyde (2p) and comparing it with conventional method (CM). The synthesized compounds were characterized by various spectroscopic techniques viz., IR, LC-HRMS, 1H NMR and 13C NMR. In MM, reaction was completed in 1-5 min as compared to CM requiring 10-40 h. All synthesized compounds were screened for antifungal activity against Sclerotium rolfsii and Alternaria solani and for nematicidal activity against root-knot nematode, Meloidogyne incognita. In vitro studies revealed that compound 3o (ED50 = 23.24 mg L-1) was found to be most active against S. rolfsii. But in case of A. solani, compound 3c (ED50 = 29.9 mg L-1) showed highest activity. The screening for nematicidal activity revealed that the compound 3b was more potent with LC50 values of 10.67, 7.30 and 4.55 ppm at 24 h, 48 h and 72 h respectively. 2D-Quantitative Structural Activity Relationship (2D-QSAR) analysis of these ferrocenyl chalcones was carried out by developing three different models namely Partial Least Squares (PLS, Model 1), Multiple Linear Regression (MLR, Model 2) and Principal Component Regression (PCR, Model 3). Statistical significance and predictive ability of these models were assessed by internal and external validation and also verified by leave one-out cross-validation. QSAR study revealed that MLR for S. rolfsii (r2 =0.999, q2= 0.996), PLS for A. solani (r2 =0.934, q2= 0.749) and PCR for M. incognita (r2 =0.878, q2= 0.772) is the best model. The physico-chemical parameters were calculated using VLife MDS 4.6 software. QSAR study could be employed for structure optimization to achieve better activity.